Characteristics of innovating users in a consumer goods field: An empirical study of sport-related product consumers - Christian Lüthje (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2000)
We report on a survey of the innovation activities and characteristics of 153 users of outdoor-related consumer products. We find a high level of innovation by these consumers. Thirty-seven percent report that they have developed ideas for new or improved products, and more than 9% report building product prototypes or even marketable products. We also find that innovating users can be reliably distinguished from non-innovating ones by characteristics such as the benefit they expect from using their innovations and the level of expertise they have in their sport. Taken together, these two findings - frequent innovation by consumers and the possibility to identify efficiently those who innovate - imply that innovation by users can be an important source of new product ideas for consumer goods companies. Effective utilization of this resource will require significant changes in idea generation methodologies for many consumer good firms.
urn:nbn:de:gbv:830-opus-1556
Keywords: 650; Produktinnovation; Produktentwicklung; Lead User